2013
DOI: 10.1155/2013/760272
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Intervention Criterias for Controlling Sever Bleeding after Percutaneous Nephrolithotomy

Abstract: Objectives. To determine when emergent intervention for bleeding after percutaneous nephrolithotomy (PCNL) is required. Methods. We reviewed analysis data of 850 patients who had undergone PCNL in our center. Blood transfusion was needed for 60 (7%) patients during and/or after surgery. We routinely performed followup of the urine output per hour, blood pressure, and hemoglobin levels after PCNL. Five (0.6%) of them had severe bleeding that emergent intervention was needed. Results. The mean age of the 5 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
8
0
7
Order By: Relevance
“…Indications for embolization include clinical signs of hemodynamic instability and uncontrolled haemorrhage after conservative management [14][15][16][17][18][19][20]. Oguz et al [23] proposed that metabolic acidosis and anuria/ oliguria accompanied by a drop in haemoglobin were indications for emergent intervention. Jinga et al [24] considered that the variations of haemoglobin, together with the quantity of transfused units represented the indicator, and decided the moment when selective angiography should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for embolization include clinical signs of hemodynamic instability and uncontrolled haemorrhage after conservative management [14][15][16][17][18][19][20]. Oguz et al [23] proposed that metabolic acidosis and anuria/ oliguria accompanied by a drop in haemoglobin were indications for emergent intervention. Jinga et al [24] considered that the variations of haemoglobin, together with the quantity of transfused units represented the indicator, and decided the moment when selective angiography should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a clear indication for TAE is very important. Oguz et al recommended emergent surgical intervention should be performed if metabolic acidosis and anuria/oliguria accompanied the decrease of hemoglobin 20 . Jinga et al 21 reported that the variations of hemoglobin, together with the quantity of transfused units, is an indication for TAE.…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de las ventajas de la posición prono se destaca que provee al especialista una mayor superficie de área para elegir el sitio de punción, en particular si se desea ingresar a los cálices del polo superior; a su vez facilita mayor espacio para la manipulación del nefroscopio con una buena distensión del sistema colector, permitiendo el acceso a través del espacio avascular de Brodel sin significativo sangrado renal y con menor riesgo de lesión peritoneal o visceral. 39 Considerando las desventajas, Duty y colaboradores demostraron en su estudio que la posición prona provee menores longitudes en los trayectos de la NLP. 40 La longitud media del trayecto de la nefrostomía fue más corta en la posición prona (82,6 mm riñón derecho, 85,4 mm riñón izquierdo), en comparación con la posición supina (108,3 mm riñón derecho, 103.7 mm riñón izquierdo), lo cual fue estadísticamente significativo (p < 0,001).…”
Section: Posición Prono Tradicionalunclassified
“…8 Como ya habíamos descrito antes de realizar la punción percutánea en posición prona, los pacientes se colocan inicialmente en una posición supina de litotomía para permitir la inserción de un catéter ureteral buscando obtener una pielografía retrógrada. 39 Esa necesidad de reposicionamiento de los pacientes a la posición prona la hace menos atractiva para algunos urólogos 8 y la necesidad de un cambio adicional intraoperatorio pone en riesgo el paciente y podría prolongar el tiempo quirúrgico. 39 La posición prona está contraindicada por los anestesiólogos en los pacientes con alto riesgo cardiovascular Además, es técnicamente difícil en pacientes con deformidades anatómicas en la cadera o contracturas de la columna lumbar.…”
Section: Posición Prono Tradicionalunclassified
See 1 more Smart Citation